The Tutor's Toolkit: Categorizing and Utilizing Code-Switching Strategies for Beginner English Instruction - Nine Febrie Novitasari; Nigorakhon Ruzibaeva (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study examines the application of code-switching by a tutor in the context of English language instruction within a language course. It aims to classify the varieties of code-switching evident in the tutor's statements and elucidate their communicative roles during the instructional process. The research employs a qualitative methodology, utilizing data obtained from direct classroom observation and video recordings. A qualitative methodology, utilizing classroom observation and video documentation, was implemented. We looked at the data by putting different types and functions of code-switching into groups based on well-known theoretical frameworks. The findings indicate that the tutor utilized two forms of code-switching: inter-sentential switching, which involves switching between sentences, and intra-sentential switching, which involves switching within a sentence. The most common type was switching between sentences.The study also found that code-switching has four main purposes: changing the topic, affecting the mood, repeating something, and socializing. Among these, the topic switch function was used the most often. These results indicate that code-switching is a beneficial communication technique in English language instruction, facilitating classroom interaction and augmenting student comprehension.